2012
DOI: 10.3389/fgene.2012.00056
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miRNAs: Biological Properties and Therapeutic Potential

Abstract: MicroRNAs (miRNAs), small non-coding regulatory RNAs that regulate gene expression at the post-transcriptional level, are master regulators of a wide array of cellular processes. Altered miRNA expression could be a determinant of disease development and/or progression and manipulation of miRNA expression represents a potential avenue of therapy. Exosomes are cell-derived extracellular vesicles that promote cell–cell communication and immunoregulatory functions. These “bioactive vesicles” shuttle various molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
248
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(252 citation statements)
references
References 106 publications
(125 reference statements)
2
248
0
2
Order By: Relevance
“…123 It is still not known which exosomal factors are most important for the effects described above, but this body of results so far supports the interpretation that certain growth factors and cytokines, such as basic fibroblast growth factor, tumor necrosis factor-α, TGF-β, epidermal growth factor, heat shock proteins (HSP20, 60, and 70), and miRs known to be carried by exosomes, are, at least in part, responsible for the response. 110,124,[125][126][127][128] Ischemic preconditioning was first described by Murry et al 129 in 1986. Several factors have been shown to function in this phenomenon, including adenosine, ATP-dependent K + channels, mitochondrial transition pores, and some other factors.…”
mentioning
confidence: 99%
“…123 It is still not known which exosomal factors are most important for the effects described above, but this body of results so far supports the interpretation that certain growth factors and cytokines, such as basic fibroblast growth factor, tumor necrosis factor-α, TGF-β, epidermal growth factor, heat shock proteins (HSP20, 60, and 70), and miRs known to be carried by exosomes, are, at least in part, responsible for the response. 110,124,[125][126][127][128] Ischemic preconditioning was first described by Murry et al 129 in 1986. Several factors have been shown to function in this phenomenon, including adenosine, ATP-dependent K + channels, mitochondrial transition pores, and some other factors.…”
mentioning
confidence: 99%
“…Since the first report demonstrating the presence of mRNA and microRNA in exosome preparations (Valadi et al , 2007 ), thousands of different mRNAs may be identified in exosomes derived from murine and human cells. Interestingly, some hundreds of gene transcripts were exclusively detectable in MVs/ exosomes and not in the cellular source of exosomes (Hu et al , 2012 ;L ä sser, 2012 ;Ramachandran and Palanisamy , 2012 ). This suggests that specific selection mechanism/s operate during the intracellular sorting of RNAs into exosomes (Valadi et al , 2007 ;Taylor and Gercel -Taylor, 2008 ;Rabinowits et al , 2009 ;Mittelbrunn et al , 2011 ).…”
Section: Nucleic Acidsmentioning
confidence: 99%
“…In addition to miRNAs, exosomes can contain proteins and mRNAs, and thus exosomes have been shown to constitute a mode of intercellular communication selectively transmitting several types of information between cells. These "bioactive shuttle vesicles" are known to transfer these various molecules, including the miRNAs, to recipient cells, and to promote cell-cell communication and immunoregulatory functions (58,59).…”
Section: Serum Markers For Ovarian Cancermentioning
confidence: 99%